Evaluation : a systematic approach - Rossi, Peter H. (California SAGE, 2019)
"Evaluation: A Systematic Approach is the bestselling comprehensive introduction to the field of program evaluation, covering the range of evaluation research activities used in appraising the design, implementation, effectiveness, and efficiency of social programs. Relied upon as the "gold standard" by professors, students, and practitioners, this new Eighth Edition includes five new or substantially revised chapters, including a new practical chapter on planning an evaluation, and a major re-organization of the book's content to better serve the needs of program evaluation courses
Includes bibliographical references (pages 323-330) and index.
Keywords: Evaluation research (Social action programs)